2014
DOI: 10.31686/ijier.vol2.iss11.261
|View full text |Cite
|
Sign up to set email alerts
|

Need for In-Service Training for Teachers and It’s Effectiveness In School.

Abstract: This essay discusses the need for in-service training for teachers and the effectiveness of in-service training in school. In-service training act as a catalyst for a teacher’s effectiveness. It is also a way of updating teachers’ skills and knowledge for improving teaching and learning which lead to better job performance. In-service training is important for teachers to face new challenges and changes in the education world. In-service training is also a fundamental aspect to improve teacher professionalism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 2 publications
0
25
0
4
Order By: Relevance
“…This finding is consistent with the result of a study done in Malaysia where in-service training had improved ECTP by empowering teachers to be systematic and logical. 19 The current study showed that teaching 5-12 students per clinical unit is positively associated with ECTP. This result is consistent with the result of a study done at the Department of Midwifery in Mekelle University that suggested 5-8 students per clinical unit to effectively provide clinical education.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This finding is consistent with the result of a study done in Malaysia where in-service training had improved ECTP by empowering teachers to be systematic and logical. 19 The current study showed that teaching 5-12 students per clinical unit is positively associated with ECTP. This result is consistent with the result of a study done at the Department of Midwifery in Mekelle University that suggested 5-8 students per clinical unit to effectively provide clinical education.…”
Section: Discussionmentioning
confidence: 50%
“…We developed part of the questionnaire that encompass independent variables by incorporating both locally relevant factors that were not studied previously and factors identified by different studies conducted elsewhere. [19][20][21][22] To do this we determined the variables depending on the objective of the study; followed by formulating, sequencing, formatting the questions, and finally, we pre-tested as part of the whole questionnaire. The part of the questionnaire used to measure the outcome variable was adopted from the clinical teachers' effectiveness inventory tool developed by Mogan & Knox.…”
Section: Data Collection Procedures Instrumentmentioning
confidence: 99%
“…Thus, there is a greater need to rapidly transform teachers' professional efficiency and professional development demands to continue with their occupational practices as well as to adapt to them new conditions. For example, teachers are expected to develop both individually and professionally to meet the requirements of the current age as well as to increase the performance of their institutions (Aydın, 2011a;Omar, 2014). Over time, the professional development process can lead to the transformation of teachers' beliefs and teaching practices, which allows them to focus on changes that will ultimately increase the success of their students' (Martin et al, 2019).…”
Section: The Concept Of Professional Developmentmentioning
confidence: 99%
“…Professional development needs are the gaps that exist between the competencies employees already have and those competencies they need to gain to work effectively and satisfactorily in both the present and future. Needs analysis is a process 430 that can be utilized to identify the differences between employees' current and expected competencies (Omar, 2014). In this respect, doing needs analysis makes it possible for teachers to receive training that is more suitable and applicable for the structure of their classes (Bayrakçı, 2009).…”
Section: Professional Development Needs Analysis Techniquesmentioning
confidence: 99%
“…The in-service teacher training programs are conducted to link any program given to teachers who are already working in schools to update and to increase their knowledge, technical skills and so on [9]. Several factors that contribute to the effectiveness of in-service training are the administrator's role, teachers' attitudes, training needs and strategies for conducting in-service training [10]. In line with this opinion, Vaillant & Manso argue that training institutions must have the leadership, authority, budget, personnel, infrastructure, and resources for learning preparation to reach state standards [11].…”
Section: Introductionmentioning
confidence: 99%